Immune response of the Antarctic sea urchin Sterechinus neumayeri: cellular, molecular and physiological approach. - Gonzalez-Aravena, Marcelo (2015)
In the Antarctic marine environment, the water temperature is usually between 2 and - 1.9 °C. Consequently, some Antarctic species have lost the capacity to adapt to sudden changes in temperature. The study of the immune response in Antarctic sea urchin (Sterechinus neumayeri) could help us understand the future impacts of global warming on endemic animals in the Antarctic Peninsula. In this study, the Antarctic sea urchins were challenged with lipopolysaccharides and Vibrio alginolitycus. The cellular response was evaluated by the number of coelomocytes and phagocytosis. A significant increase was observed in red sphere cells and total coelomocytes in animals exposed to LPS. A significant rise in phagocytosis in animals stimulated by LPS was also evidenced. Moreover, the gene expression of three immune related genes was measured by qPCR, showing a rapid increase in their expression levels. By contrast, these immune genes showed a depression in their expression by a thermal effect at 5 and 10 °C. In addition, during bacterial injection, the oxygen consumption was higher in challenged animals. Our results showed that the immune response in the Antarctic sea urchin may be affected by acute thermal stress and that this immune response has a metabolic cost.